1981
DOI: 10.1073/pnas.78.12.7825
|View full text |Cite
|
Sign up to set email alerts
|

Isolated horizontal cells from carp retina demonstrate dopamine-dependent accumulation of cyclic AMP.

Abstract: Horizontal cells of the carp retina were separated from other retinal cell types by using enzymatic dissociation and velocity sedimentation at unit gravity. Fractions containing horizontal cells were tested for their ability to accumulate cyclic AMP in the presence of various putative neurotransmitters. Micromolar concentrations ofdopamine, when added in the presence of 3-isobutyl-1-methylxanthine, stimulated cyclic AMP accumulation in these isolated cells. The dopamine-dependent accumulation of cyclic AMP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

1984
1984
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 20 publications
1
62
1
Order By: Relevance
“…When the catalytic subunit of the cyclic AMP-dependent protein kinase was included in the patch pipette solution, little coupling was observed, whereas when a kinase inhibitor was included, coupling did not respond to dopamine (Lasater, 1987). In a separate series of experiments, dopamine (1-300 /IM) increased the cyclic AMP content of horizontal cells collected from dissociated retinas (Van Buskirk & Dowling, 1981).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…When the catalytic subunit of the cyclic AMP-dependent protein kinase was included in the patch pipette solution, little coupling was observed, whereas when a kinase inhibitor was included, coupling did not respond to dopamine (Lasater, 1987). In a separate series of experiments, dopamine (1-300 /IM) increased the cyclic AMP content of horizontal cells collected from dissociated retinas (Van Buskirk & Dowling, 1981).…”
Section: Introductionmentioning
confidence: 93%
“…Van Buskirk & Dowling (1981) have shown that high concentrations of dopamine (more than 1 ,UM) increase cyclic AMP content in isolated horizontal cells when phosphodiesterase is simultaneously inhibited with 2 mM-IBMX. Our experiments demonstrate that 100 nM-dopamine can uncouple by up to 80 % in the absence of IBMX.…”
Section: S H Devriesande a Schwartzmentioning
confidence: 99%
“…In teleost fish, retinal dopamine appears to be confined to the inter-plexiform cells, neurons that receive their input from amacrine cells in the inner plexiform layer and send the majority of their output to horizontal and bipolar cells in the outer plexiform layer (Dowling and Ehinger, 1978). Dopamine has been shown to stimulate adenylate cyclase activity in the fish retina (Dowling and Watling,198 1;Watling and Dowling,198 1) and in isolated retinal horizontal cells (Van Buskirk and Dowling, 1981). In addition, dopamine has been reported to decrease light responsiveness of horizontal cells (Hedden and Dowling, 1978;Mange1 and Dowling, l985;Negishi and Drujan, 1979a), alter horizontal cell receptive field size by decreasing electrotonic coupling between cells (Cohen and Dowling, 1983;Gerschenfeld et al, 1982;Lasater and Dowling, 1985;Negishi and Drujan, 1978;Teranishi et al, 1983), and inhibit K+-stimulated GABA release from horizontal cells (O'Brien and Dowling, 1985;Yazulla and Kleinschmidt, 1982).…”
mentioning
confidence: 99%
“…GABA, the neurotransmitter of retinal horizontal cells in Xenopus (14), has no effect on phosphoinositide metabolism in this cell. Dopamine, which has been shown to stimulate adenylate cyclase in carp retinal horizontal cells (32,34), has no effect on phosphoinositide metabolism. Likewise, norepinephrine, which is known to elicit a phosphoinositide response in other neural tissues (17,30), was not effective in producing a phosphoinositide response in the retina.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, neurotransmitter-stimulated phosphoinositide turnover is most likely associated with cellular activities other than transmitter release . In horizontal cells from carp retina, the regulation of adenylate cyclase activity has been demonstrated to be mediated by input from dopaminergic interplexiform cells (6,32,34) as well as by vasoactive intestinal peptide (VIP) (15,33). Since the effects of these two compounds on accumulation of cyclic AMP in isolated horizontal cells is not additive (12), it is likely that receptors for both are on the same cell .…”
Section: Discussionmentioning
confidence: 99%